Applications of Gold Nanoparticles in the Detection and Identification of Infectious Diseases and Biothreats - Lin, Meihua (Adv Mater, 2013)
The situation of infectious diseases and biothreats all over the world remains serious. The effective identification of such diseases plays a very important role. In recent years, gold nanoparticles have been widely used in biosensor design to improve the performance for the detection of infectious diseases and biothreats. Here, recent advances of gold‐nanoparticle‐based biosensors in this field are summarized.